Undoing the Past. Necessitas per accidens e logica temporale nel De divina omnipotentia - Roberto Limonta (Noctua, 2021)
Peter Damian’s letter 119 De divina omnipotentia is characterized by two main issues: the dilemma about the God’s capacity to restore virginity to a woman and the question about the possibility of undoing the past. Despite the interweaving between these topics, they have to be distinguished in several respects. Aim of the paper will be, firstly, to isolate the two questions, starting with their textual loci; secondly, to focus on the dilemma about the divine capacity to undoing the past, showing that the key of Peter Damian’s argument is the concept of eternity as an epistemic principle, that allows him to define the omnipotence, in the case of the action on temporal necessity, as a sort of second level property of God; finally, to compare the Damian’s solution with some contemporary theories, developed during the debate on omnipotence in the second half of the 20th century, in order to find continuity and discontinuity factors that can help to better understand the coherence and effectiveness of medieval and contemporary arguments.